Alkaline Earth Metal‐Mediated Highly Iso‐selective Ring‐Opening Polymerization of rac‐Lactide. Issue 6 (20th February 2020) - Bhattacharjee, Jayeeta; Harinath, Adimulam; Sarkar, Alok; Panda, Tarun K.
Abstract: Alkaline earth (Ae) metal complexes of the aminophosphine borane ligand are highly active and iso‐selective catalysts for the ring‐opening polymerization (ROP) of rac ‐lactide (LA). The polymerization reactions are well controlled and produce polylactides with molecular weights that are precise and narrowly distributed. Kinetic studies reveal that the ROP of rac ‐LA catalyzed by all Ae metal complexes had a first‐order dependency on LA concentration as well as catalyst concentration. A plausible reaction mechanism for Ae metal complex‐mediated ROP of rac ‐LA is discussed, based on controlled kinetic experiments and molecular chain mobility. Abstract : Alkaline earth metal amido‐phosphine borane complexes catalyze the ROP of rac ‐lactide with high activity and iso‐selectivity.